2013
DOI: 10.1002/lary.24494
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of the larynx in adult obstructive sleep apnea?

Abstract: The endolarynx warrants consideration in the pathophysiology of OSA, particularly as it relates to sensory dysfunction and epiglottic obstruction. Patients with head and neck cancer of the laryngopharynx are at significant risk of OSA. Further research is needed to better understand and heighten awareness of the intimate role that the larynx may play in OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
2
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 37 publications
0
64
2
11
Order By: Relevance
“…Only two patients with a slightly disabling WD had an OSAH syndrome with an AHI of >30/h, which most probably was caused by obesity (as Page 10 of 25 both had a BMI of >30 kg/m2). These results in patients with WD are in contrast to multiple system atrophy in which a high prevalence of dysarthria, nocturnal stridor, and OSAH have been observed [38,39] and to intracerebral hemorrhage with dysarthria in which an association to SDB has been reported [40].…”
Section: Vpsg Data From Patients With Wd and Healthy Controlscontrasting
confidence: 72%
“…Only two patients with a slightly disabling WD had an OSAH syndrome with an AHI of >30/h, which most probably was caused by obesity (as Page 10 of 25 both had a BMI of >30 kg/m2). These results in patients with WD are in contrast to multiple system atrophy in which a high prevalence of dysarthria, nocturnal stridor, and OSAH have been observed [38,39] and to intracerebral hemorrhage with dysarthria in which an association to SDB has been reported [40].…”
Section: Vpsg Data From Patients With Wd and Healthy Controlscontrasting
confidence: 72%
“…In the case of primary epiglottis collapse, CPAP may aggravate airway obstruction by further pushing the epiglottis down into the laryngeal inlet. Dedhia et al showed that the majority of adult patients who are unable to tolerate CPAP have multilevel obstruction, of which 15% presented with primary epiglottis obstruction of the hypopharynx …”
Section: Resultsmentioning
confidence: 99%
“…Some studies demonstrate that CPAP may be ineffective in patients who have a severely floppy epiglottis because the pressure may further push the epiglottis into the laryngeal inlet. [24][25][26] The extent to which epiglottic collapse contributes to CPAP failure or non-adherence is not known and is an area of interest for future study. Although surgical resection or trimming of the epiglottis may be an option, no controlled studies have reported the efficacy of this approach, and the potential for side effects such as aspiration are not trivial.…”
Section: Discussionmentioning
confidence: 99%